The differential impacts of PEPFAR transition on private for-profit, private not-for-profit and publicly owned health facilities in Uganda - Alan Wilhelm, Jess; Paina, Ligia; Qiu, Mary; Zakumumpa, Henry; Bennett, Sara (Health policy and planning, 2020)
While transition of donor programs to national control is increasingly common, there is a lack of evidence about the consequences of transition for private health care providers. In 2015, President’s Emergency Plan for AIDS Relief (PEPFAR) identified 734 facilities in Uganda for transition from PEPFAR support, including 137 private not-for-profits (PNFP) and 140 private for-profits (PFPs). We sought to understand the differential impacts of transition on facilities with differing ownership statuses. We used a survey conducted in mid-2017 among 145 public, 29 PNFP and 32 PFP facilities reporting transition from PEPFAR. The survey collected information on current and prior PEPFAR support, service provision, laboratory services and staff time allocation. We used both bivariate and logistic regression to analyse the association between ownership and survey responses. All analyses adjust for survey design. Public facilities were more likely to report increased disruption of sputum microscopy tests following transition than PFPs [odds ratio (OR)¼5.85, 1.79–19.23, P¼0.005]. Compared with public facilities, PNFPs were more likely to report declining frequency of supervision for human immunodeficiency virus (HIV) since transition (OR¼2.27, 1.136–4.518, P¼0.022). Workers in PFP facilities were more likely to report reduced time spent on HIV care since transition (OR¼6.241, 2.709–14.38, P<0.001), and PFP facilities were also more likely to discontinue HIV outreach following transition (OR¼3.029, 1.325–6.925; P¼0.011). PNFP facilities’ loss of supervision may require that public sector supervision be extended to them. Reduced HIV clinical care in PFPs, primarily HIV testing and counselling, increases burdens on public facilities. Prior PFP clients who preferred the confidentiality and service of private facilities may opt to forgo HIV testing altogether. Donors and governments should consider the roles and responses of PNFPs and PFPs when transitioning donor-funded health programs.
Keywords: HIV/AIDS; Private health providers; President’s Emergency Plan for AIDS Relief; Development assistance for health; Sub-Saharan Africa